Case Report: Paraneoplastic psoriasis in thymic carcinoma - Mix, Lucas; Knoll, Manuel; Häring, Max-Felix; Bethge, Wolfgang Andreas; Schröder, Jan C.; Forchhammer, Stephan; Krumm, Patrick; Schürch, Christian M.; Schaller, Martin; Lengerke, Claudia (Frontiers in Oncology, 2023)
Thymic carcinomas are exceedingly rare and very aggressive malignancies of the anterior mediastinum. While thymomas exhibit a high association with paraneoplastic syndromes, these phenomena are a rarity in thymic carcinomas. In general, acanthotic syndromes such as acroceratosis neoplastica and acanthosis nigricans maligna are commonly observed as paraneoplastic phenomena in patients with carcinomas. In contrast, psoriasis vulgaris, another acanthotic disease, rarely occurs as a paraneoplasia. We report the case of a 36-year-old patient with progressive thymic carcinoma (undifferentiated carcinoma, T3N2M1a) and paraneoplastic psoriasis occurring ten months before the initial diagnosis of the carcinoma. Over the course of the disease, new psoriatic flares heralded relapse or progression of the carcinoma. To our knowledge, this is the first reported case of paraneoplastic psoriasis in thymic carcinoma.